Training and Development on Promotional Pricing Through Marketing Capability of Employees in an ISP Company - Noraga, Gilang Bhirawa; Hurriyati, Ratih; Dirgantari, Puspo Dewi (Commercium : Journal of Business and Management, 2026)
This study analyzes the influence of Training and Development on Promotional Pricing with Marketing Capability as a mediating variable in Internet Service Provider (ISP) companies in the Suciayumajakuning area (Subang, Cirebon, Indramayu, Majalengka, and Kuningan). The research is motivated by competitive challenges among ISPs in designing effective promotional pricing strategies through strengthened human resource competencies. This study extends previous models by integrating human capital and dynamic capability perspectives within the ISP industry context. Unlike prior studies that predominantly focus on manufacturing or export-oriented sectors, this research addresses the less-explored ISP industry, which has high service intangibility and strong price sensitivity. with theoretical approaches from Human Capital Theory, Dynamic Capability Theory, and Resource-Based View.The study employed a quantitative approach using Structural Equation Modeling Partial Least Squares (SEM-PLS) with 150 ISP marketing respondents. The measurement model met validity and reliability criteria (loadings 0.70–0.88; AVE > 0.50; CR > 0.90). The findings show that Training and Development significantly affects Marketing Capability (β = 0.613; p < 0.001), Marketing Capability significantly affects Promotional Pricing (β = 0.582; p < 0.001), and Training and Development directly influences Promotional Pricing (β = 0.176; p < 0.05). The indirect effect (β = 0.357) confirms Marketing Capability as a significant mediator. Training and development enhance promotional pricing effectiveness both directly and through improved marketing capability. Practically, ISPs should strengthen data-driven and digital marketing training programs to sustain competitiveness.